(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3eMeO Hf SdjeGf Hf bWQT Hf JQcGf TGg s)
(3ChdgG (B:s
(3HGH GdWGA aUd GdCda bhdg (B: (3BHW (B: (3GdEHW eG JMJ GdLfGM HPcQ hjDfK hGdLeY BHGW s
(3BNQgG (B:s
(3ef HGH GdYjf aUd GdHGA bhdg (B: (3hHGjYJg ef GdHjY hGdHjYI LejYG hjbGd CjVkG Efg dMSf GdHjYI ef GdHjY eKd GdQcHI hGdLdSI Je GdLRA GdNGeS jJdhg ai GdSGOS aUd GdJGA hGdMeO ddg s
(3fSNI KGefI YTQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B39 s
Keywords: (3GddZIs